Dynamics Of The Relation Between Latin America And China: Cluster Analysis, 2005–2018 (2020)
Literature discusses the symbiosis between financing loans granted by China to Latin America and exports from this region to China. This paper contributes to this literature by providing empirical evidence on the relation be- tween Latin American countries and China by creating a typology of countries based on different key aspects such as trade, commodity dependence, debt, environment, and institutionalism in four years over time (2005, 2010, 2015, and 2018). The dependence of countries on financing from China is taken into account, given the limited access to international markets as well as how aspects of government corruption and stability impact such dynamics. The contrast between countries and indicators shows that the relation between China and Latin America involves different aspects beyond bilateral trade.